Notes about contemporary peruvian documentary - Varotto, Viola (2018)
This article is a summary of the current situation on the Peruvian contemporary documentary and an analysis of the forms of audiovisual language management, the promotion of production, as well the training spaces. It proposes, as a reminder, some contemporary filmmakers whose works have been recognized in the local and international media. Finally, it delineates the profile of the contemporary filmmaker.